Temperature Control of Mussel‐Inspired Chemistry toward Hierarchical Superhydrophobic Surfaces for Oil/Water Separation. Issue 2 (5th December 2016) - Wang, Yanbing; Shang, Bin; Hu, Xiaoxi; Peng, Bo; Deng, Ziwei
Abstract : By adopting polydopamine chemistry, a single‐step approach is introduced toward hierarchical surfaces with tunable surface wetting properties via adjusting the reaction temperature. After the hydrophobic surface decoration, the tunable superhydrophobicity of the surfaces is achieved. This tunability has been realized on a series of materials with different surface geometries, including silica nanospheres and microrods, silicon wafer, stainless steel mesh, and melamine‐formaldehyde sponge. These superhydrophobic mesh and sponge are ideal candidates for collecting various oils/organic solvents from water, because not only they exhibit high absorption/separation capacity, excellent selectivity, and extraordinary recyclability, but also they are highly chemically resistant, environmentally stable and mechanically durable. This whole procedure is straightforward, cost‐effective, green, and material‐ and surface geometry‐independent, more importantly, the obtained surface morphology is tunable, providing more opportunities to cater the demands from fundamental and practical fields. Abstract : Inspiration from mussel‐inspired polydopamine chemistry and superhydrophobic hierarchical surface of lotus leaf, a facile and versatile strategy is realized to decorate various surfaces with controllable superhydrophobicity. And the as‐prepared superhydrophobic commercial materials facilitate the applications in oil collection and oil/water separation.